Life Cycle of a Tree, The. - Kalman, Bobbie (New York, NY : Crabtree Publishing, 2002)
Text and photographs describe basic facts about trees, their function in a forest, and how they benefit animals, people and the environment.
Keywords: Trees - Juvenile literature; Trees - Life Cycle - Juvenile literature; Smithyman, Kathryn; Bedell, Barbara, ill